Pemanfaatan Pedestrian Ways di Koridor Komersial di Koridor Jalan Pemuda Kota Magelang - Setyowati, Marcelina Dwi (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2017)
Pedestrian ways are a means to protect pedestrians from the dangers of motor vehicles. However, due to poor arrangement, safe, comfortable and difficult to access cause pedestrian ways become less regular and segmented, causing conflict in the utilization of space.Pemuda street Corridor is a strategic commercial corridor, becoming a shopping center and economic center in Magelang City. In 2011, the road corridor development was conducted, ie the non-motorized lanes were integrated into the pedestrian ways so that it became wider. This led to conflicts in the utilization of road spaces such as misuse of pedestrian paths into motor vehicle parking areas, and road bagiantation problems that caused a gap in the number of pedestrians in the area. This study found that factors of utilization of pedestrian ways in influential commercial corridors on Jalan Pemuda are convenience, accessibility, land use and activity, safety and regional identity. The purpose of this research is to find the characteristics and factors that can influence the utilization of pedestrian ways in the appropriate commercial corridor in order to solve the problems that arise so as to maximize the utilization of pedestrian ways in the area.The method used in this study is a qualitative deductive method. The method used to find problems in the field then made the framework of research and process it quantitatively to determine the qualitative results.Keywords: pedestrian ways, street, commercial corridor